Response of the low latitude geomagnetic field to the major proton event of November 2001 - Alex, S.; Pathan, B.M.; Lakhina, G.S. (My University, 2005)
A major solar flare eruption occurred at 16:20 UT on 4 November 2001, followed by strong solar radiation storm and proton event recorded by the SOHO and other interplanetary satellites. Coronal mass ejection associated with the flare event triggered an interplanetary shock, which impacted the geomagnetic field after about 33 h. The shock impact was quite intense to produce a SSC magnitude of ∼80 nT in the low latitude ground magnetic records followed by sharp and deep main phase (Dst ∼−300 nT) in the first stage, following the density (Np) enhancement. High time resolution digital magnetic field data from the equatorial and low latitude stations in India are analyzed to study the influence of various IP parameters on the intensity and duration of the magnetic storm. A double step storm was found to be in progress caused by the multiple injections. During the period of recovery, after a period of 8 h, a third stage of depression in the ground magnetic field was set in, which corresponded to the southward directed Bz. The energy transfer processes associated with the event is presented.
Keywords: Solar flare; Proton event; Magnetic storm; Geomagnetic field